Faith in schools? : autonomy, citizenship, and religious education in the liberal state - MacMullen, Ian, 1976- (Princeton University Press, 2007)
Should a liberal democratic state permit religious schools? Should it fund them? What principles should govern these decisions in a society marked by religious and cultural pluralism? In Faith in Schools?, Ian MacMullen tackles these important questions through both political and educational theory, and he reaches some surprising and provocative conclusions. MacMullen argues that parents' desires to educate their children "in the faith" must not be allowed to deny children the opportunity for ongoing rational reflection about their values. Government should safeguard children's interests in de.